KOS - kinetic origami surface - Osório, F.; Paio, A.; Oliveira, S. (Proceedings of the 19th International Conference on ComputerAided Architectural Design Research in Asia CAADRIA 2014, 2014)
In an increasingly technological, informed and demanding society Architecture should be able to answer to its space require-ments using materials and technological resources that today has at its service. Kinetic systems have been used by architects as an approach that embeds computation intelligence to create flexible and adaptable architectural spaces according to users’ changing needs and desires. This paper describes one possible way of exploring kinetic systems to develop a foldable surface with geometric patterns based on the rules of rigid origami. This surface aims to take advantage of the elastic ca-pacities given to a planar material by its folding. After folding the sur-face can assume different forms in order to create a range of spatial configurations ordered by a user through a remote control.